1990
DOI: 10.1111/j.1432-1033.1990.tb15606.x
|View full text |Cite
|
Sign up to set email alerts
|

A 31P‐nuclear‐magnetic‐resonance study of NADPH–cytochrome‐P‐450 reductase and of the Azotobacter flavodoxin/ferredoxin‐NADP+ reductase complex

Abstract: 'P-nuclear-magnetic-resonance spectroscopy has been employed to probe the structure of the detergentsolubilized form of liver microsomal NADPH -cytochrome-P-450 reductase. In addition to the resonances due to the FMN and FAD coenzymes, additional phosphorus resonances are observed and are assigned to the tightly bound adenosine 2'-phosphate (2'-AMP) and to phospholipids. The phospholipid content was found to vary with the preparation; however, the 2'-AMP resonance was observed in all preparations tested. In ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…This distinct domain arrangement is consistent with results from further studies in which each domain was expressed independently (14), and unfolding of the polypeptide was correlated with the release of each individual flavin (15). CPR has been studied extensively by a number of biophysical methods, including EPR spectroscopy (16,17), time-resolved fluorescence spectroscopy (18,19), 31 P NMR (20,21), and resonance Raman spectroscopy (22). Despite these intensive studies, little has been determined about physical and electronic interactions between FMN, FAD, and NADPH and interactions between CPR and its electron transfer partners.…”
supporting
confidence: 80%
“…This distinct domain arrangement is consistent with results from further studies in which each domain was expressed independently (14), and unfolding of the polypeptide was correlated with the release of each individual flavin (15). CPR has been studied extensively by a number of biophysical methods, including EPR spectroscopy (16,17), time-resolved fluorescence spectroscopy (18,19), 31 P NMR (20,21), and resonance Raman spectroscopy (22). Despite these intensive studies, little has been determined about physical and electronic interactions between FMN, FAD, and NADPH and interactions between CPR and its electron transfer partners.…”
supporting
confidence: 80%
“…EPR spectroscopy (29,30), timeresolved fluorescence spectroscopy (31, 32), 31P NMR spectroscopy (10,(33)(34)(35)(36), and resonance Raman spectroscopy (37,38) *To whom reprint requests should be addressed.…”
mentioning
confidence: 99%
“…In contrast, the absence of any effect of manganese is interpreted as an indication that the phosphorus nucleus is buried deeply enough in the protein interior to preclude the influence of the paramagnetic ion. In addition, the observation of an increase in intensity as a direct consequence of more efficient spin‐lattice relaxation, with each resonance being less attenuated by the effects of incomplete relaxation between pulses has been observed upon addition of Mn(II) for cytochrome P450 reductase [17–19]. This observation indicated that the phosphate‐containing regions of protein‐bound FMN and FAD were shielded from interaction with bulk solvent, but were still sensitive to the influence of paramagnetic ions.…”
Section: Resultsmentioning
confidence: 96%
“…The three main phosphorus resonances observed were easily attributed to the phosphate groups of bound FMN and bound FAD from their chemical shifts and by comparison with 31 P‐NMR spectra obtained with cytochrome P450 reductase [17–19]. However, the exact value of the different chemical shifts differs from those observed in cytochrome P450 reductase suggesting that the environment of the flavin phosphate groups, in SiR‐FP, are somewhat different from that in cytochrome P450 reductase.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation